2004
DOI: 10.1038/sj.eye.6701708
|View full text |Cite
|
Sign up to set email alerts
|

Immediate pars plana vitrectomy for dislocated intravitreal lens fragments during cataract surgery

Abstract: Purpose To assess the outcome of patients who underwent instantaneous pars plana vitrectomy for dislocated lens fragments during cataract surgery. Methods The medical records of 29 patients who underwent immediate pars plana vitrectomy for dislocated lens fragments at the same sitting of phacoemulsification surgery were reviewed. Data including patients' demographics, preoperative and postoperative vision, risk factors for lens fragment dislocation, and intraoperative and postoperative complications were recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 26 publications
2
17
0
Order By: Relevance
“…However, the development of secondary glaucoma was observed in all patients in groups B and C. This is in agreement with the findings of Kageyama et al [3], Kim et al [6] and Lai et al [20], in that none of their patients who underwent vitrectomy for dislocated lens fragments on the same day as cataract surgery developed secondary glaucoma. This is an important finding because secondary glaucoma has been reported in 5–41% of subjects in previous studies in which pars plana vitrectomy was performed at a later time [4, 6,9,10,11,12,13,14,15].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…However, the development of secondary glaucoma was observed in all patients in groups B and C. This is in agreement with the findings of Kageyama et al [3], Kim et al [6] and Lai et al [20], in that none of their patients who underwent vitrectomy for dislocated lens fragments on the same day as cataract surgery developed secondary glaucoma. This is an important finding because secondary glaucoma has been reported in 5–41% of subjects in previous studies in which pars plana vitrectomy was performed at a later time [4, 6,9,10,11,12,13,14,15].…”
Section: Discussionsupporting
confidence: 82%
“…In our study, none of the patients in group A or B developed cystoid macular edema, whereas 3 of 11 patients (27%) in group C did. This is similar to the findings of Kim et al [6] and Lai et al [20], in which no patient developed postoperative cystoid macular edema after undergoing vitrectomy on the same day as complicated cataract surgery. Margherio et al [10] found that 27% of their patients developed postoperative cystoid macular edema after vitrectomy as a late postoperative complication.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Timing of Vitreoretinal Surgery: 13,14,15 Ideally in the same sitting. Early surgery is preferred if significant nuclear matter is retained, it reduces the incidence of post-operative glaucoma and is associated with better visual outcomes…”
Section: Intra-operative Managementmentioning
confidence: 99%
“…Immediate pars plana vitrectomy has advantages for the patient and for the eye. 33 Secondary glaucoma is an important complication of retained lens matter and this is prevented or reversed by early vitrectomy. 34 However, deferment of surgery for 2-3 weeks may allow lens material to become softer and easier to remove.…”
Section: Management: the Eyementioning
confidence: 99%